Combined Effects of Microplastics and Nitrogen on Bivalve-mediated Biogeochemical Cycling - Foreman, Saskia; Allan, Bridie; Sabadel, Amandine; Savage, Candida (Wiley, 2026)
Estuary health is declining globally due to an increase in anthropogenic stressors including microplastics and nutrient loading. These stressors are often studied individually; however, it is vital to understand their combined effects on coastal ecosystems to inform ecosystem-based management. This is the first study to evaluate the multi-stressor responses of microplastics (polyethylene microbeads) and nitrogen loading in intertidal soft sediment communities. In this laboratory experiment, the individual and combined effects of microplastics and nitrogen were assessed on biogeochemical processes mediated by the bivalve, Macomona liliana. This deep-dwelling bivalve feeds on microphytobenthos at the sediment surface and augments porewater nutrients through its behavior. Ammonium porewater concentrations increased ~ 260% with the addition of nitrogen; however, this porewater increase did not carry over to the multiple stressor treatment. Further, sediment-water nitrogen effluxes tended to be higher with the addition of single stressors under light conditions, with a significant increase in the multiple stressor treatments. These findings suggest that nitrogen processing responses emerge under multiple stressor conditions. Furthermore, sediment profile image analysis revealed a significant negative effect of multiple stressors on sediment redox conditions. Lastly, bivalves exposed to multiple stressors had approximately 1% more docosahexaenoic acid (DHA, 22:6n-3) as a proportion of their total fatty acids in their tissue compared to those under control conditions, reflecting the low levels of DHA found in the microphytobenthos under multiple stressor conditions. The study highlights the complex interactions between subtle shifts in food quality and infaunal behavior that affect nutrient cycling at the sediment–water interface in coastal ecosystems.
Keywords: 4102 Ecological Applications; 31 Biological Sciences; 3103 Ecology; 4105 Pollution and Contamination; 41 Environmental Sciences; 14 Life Below Water; 04 Earth Sciences; 05 Environmental Sciences; 06 Biological Sciences; Marine Biology & Hydrobiology; 31 Biological sciences; 37 Earth sciences; 41 Environmental sciences